Determinativproduktion: Fra Brocas afasi til en lingvistisk teori om, hvad grammatik er - Boye, Kasper; Rosenbech Nielsen, Sarah; Ishkhanyan, Byurakn (Ny forskning i grammatik, 2019)
This paper summarizes recent experiments examining the production of grammatical and lexical determiners in healthy individuals and individuals with agrammatic aphasia. The experiments discussed employ a design in which the Danish grammatical indefinite article en/et is contrasted with the lexical numeral en/et. The results show that articles are harder to produce than numerals. In agrammatic speech the difference is reflected in a higher proportion of omissions of articles. In healthy speech the difference is reflected in increased response times and decreased accurary rates for articles. The results are interpreted in light of a usage-based and functional theory of grammar, in which grammatical items are defined as signs that are by convention discursively secondary and structurally dependent.